2007
DOI: 10.1002/chin.200749049
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐Active Calixarenes: Toward “Gating” Transmembrane Anion Transport.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, the cavity of calix[4]­arenes is believed to be too small for anions to pass through, and the authors therefore suggest that the ion channel activity is due to a self-assembled framework that was observed in a solid-state crystal structure of analogous calixarenes. Later studies showed that analogues of 309 in the paco and cone conformation are also able to transport chloride anions and that one of the arms of calixarene 309 can be left unsubstitued without loss of channel activity. , Furthermore, Davis and co-workers also found that the macrocycle is not required for ion channel activity, as acyclic analogues of 309 were also able to function as anion channels …”
Section: Transmembrane Anion Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cavity of calix[4]­arenes is believed to be too small for anions to pass through, and the authors therefore suggest that the ion channel activity is due to a self-assembled framework that was observed in a solid-state crystal structure of analogous calixarenes. Later studies showed that analogues of 309 in the paco and cone conformation are also able to transport chloride anions and that one of the arms of calixarene 309 can be left unsubstitued without loss of channel activity. , Furthermore, Davis and co-workers also found that the macrocycle is not required for ion channel activity, as acyclic analogues of 309 were also able to function as anion channels …”
Section: Transmembrane Anion Transportmentioning
confidence: 99%
“…Later studies showed that analogues of 309 in the paco and cone conformation are also able to transport chloride anions and that one of the arms of calixarene 309 can be left unsubstitued without loss of channel activity. 520,521 Furthermore, Davis and co-workers also found that the macrocycle is not required for ion channel activity, as acyclic analogues of 309 were also able to function as anion channels. 522 In recent years there have been a number of reports of intriguingly small molecules capable of forming anion channels, suggesting that it is not always necessary to develop large membrane-spanning structures to obtain anion channel activity.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…11) [67,68]. Interestingly, while 9a is active in the Cl -/NO 3 -antiport in liposome (assessed with the lucigenin assay), 9b is completely inactive.…”
Section: Channel Forming Artificial Anion Transport-ersmentioning
confidence: 97%
“…SP-loaded liposomes and, for the sake of comparison, SP-free liposomes were prepared by rehydration of a homogeneous thin film with a phosphate-buffered solution (100 mM NaNO 3 and 10 mM sodium phosphate) of lucigenin dye (0.025 mM). The subsequent extrusion and gel filtration afforded the liposomal samples that were added with 0.07 mM HCl. SP-loaded liposomes evidenced a lucigenin quenching of 3 and 13.3% with respect to the pure liposomes upon 1 or 4 UV–vis irradiation cycles, respectively (see Figure S20 of the Supporting Information and, for control experiments, see Figures S15–S19 of the Supporting Information).…”
Section: Experimental Sectionmentioning
confidence: 99%